2016
DOI: 10.1093/sleep/zsw053
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Insomnia

Abstract: Study Objectives: There is little information about familial aggregation of insomnia; however, this type of information is important to (1) improve our understanding of insomnia risk factors and (2) to design more effective treatment and prevention programs. This study aimed to investigate evidence of familial aggregation of insomnia among first-degree relatives of probands with and without insomnia. Methods: Cases (n = 134) and controls (n = 145) enrolled in a larger epidemiological study were solicited to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This also applies to a population-based cross-sectional study which showed that persons who ever suffered from insomnia had an increased chance of having relatives with insomnia compared to persons without a history of insomnia (OR = 1.57, 95% CI: 1.19–2.07) [ 20 ]. In a further study with a reconstructed cohort design, biological relatives of index persons had a higher risk of insomnia when index persons were affected with insomnia but results were not unambiguous for parents and children (RR = 1.80 (p = 0.04) for all biological relatives, 4.96 (p = 0.08) for siblings, 0.84 (p = 0.71) for parents, 1.65 (p = 0.38) for offspring) [ 21 ]. In the same study, partners of index persons were also taken into account, and the corresponding relative risk was increased but not estimated precisely (RR = 2.13, p = 0.28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also applies to a population-based cross-sectional study which showed that persons who ever suffered from insomnia had an increased chance of having relatives with insomnia compared to persons without a history of insomnia (OR = 1.57, 95% CI: 1.19–2.07) [ 20 ]. In a further study with a reconstructed cohort design, biological relatives of index persons had a higher risk of insomnia when index persons were affected with insomnia but results were not unambiguous for parents and children (RR = 1.80 (p = 0.04) for all biological relatives, 4.96 (p = 0.08) for siblings, 0.84 (p = 0.71) for parents, 1.65 (p = 0.38) for offspring) [ 21 ]. In the same study, partners of index persons were also taken into account, and the corresponding relative risk was increased but not estimated precisely (RR = 2.13, p = 0.28).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to some other studies, sleep characteristics of offspring and partners were directly assessed. Thus, reporting bias could be avoided because in earlier studies there was an indication that persons with insomnia had a tendency to overreport insomnia in relatives [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family studies in the insomnia field report a variety of statistics, making it difficult to calculate a robust estimate, but studies show that between 35% and 73% of patients with insomnia‐type phenotypes also have a relative with sleep disturbances/insomnia 13,14,40 . Using a similar metric, other family studies yield a relative risk of having insomnia of 1.8 to 4.42 in those with positive biological family history 41‐43 . Finally, other family studies have showed that around 29% to 37% of variability in stress‐related sleep disturbance, and 48% to 61% for current and lifetime insomnia disorder, is accounted for by familial factors 42,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Aim of FA analysis is to identify groups of related individuals carrying the same symptoms or disease due to some underlying shared mechanism. A wide range of diseases has been previously analyzed with FA methods (Naj and Beaty, 2017), including cancer (Tokuhata and Lilienfeld, 1963), cardiovascular disease (Feinleib et al , 1977) and more recently autoimmune disease (Kuo et al , 2015) and insomnia (Jarrin et al , 2017). The increasing availability of large pedigrees for epidemiological research provides both an opportunity and a challenge for FA analysis, especially considering that such large pedigrees are often incomplete and with no regular structure.…”
Section: Introductionmentioning
confidence: 99%